Pengembangan âMinapadi Kolam Dalamâ di Kabupaten Sleman - Lantarsih, Retno (AGRARIS: Journal of Agribusiness and Rural Development Research, 2016)
Â "Minapadi kolam dalamâ is a new invention where rice farming was integrated with fish farming. The system that introduced by Dinas Pertanian of Sleman District in 2011 was expected to increase the farmerâs income. This study aims to create the development strategy of "Minapadi kolam dalam" on target group. The method of analysis that used in this study was SWOT analysis. The development strategy of âMinapadi kolam dalam" on target group is in an aggressive position that means the development is concentrated in exploiting the opportunities and strengths.Â